2022
DOI: 10.3390/ijms232113144
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Hypoxia-Inducible Factor 1-α in Experimental Testicular Ischemia and Reperfusion: Effects of Polydeoxyribonucleotide and Selenium

Abstract: Polydeoxyribonucleotide (PDRN) is an agonist of the A2A adenosine receptor derived from salmon trout sperm. Selenium (Se) is a trace element normally present in the diet. We aimed to investigate the long-term role of PDRN and Se, alone or in association, after ischemia-reperfusion (I/R) in rats. The animals underwent 1 h testicular ischemia followed by 30 days of reperfusion or a sham I/R and were treated with PDRN or Se alone or in association for 30 days. I/R significantly increased hypoxia-inducible factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Nrf2 can also induce and regulate the composition and expression of antioxidant proteins (including CAT, SOD, and GSH), reduce the production of ROS, and maintain the redox stability of the body ( Sang et al, 2024 ; Zhang et al, 2024 ). Studies have shown that testicular I/R damage is related to the decrease in antioxidant enzymes regulated by Nrf2 ( Antonuccio et al, 2022 ). Indeed, the use of some antioxidants (including SAL) has been extensively discussed for preventing testicular injury ( Matzkin et al, 2021 ; Cai et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 can also induce and regulate the composition and expression of antioxidant proteins (including CAT, SOD, and GSH), reduce the production of ROS, and maintain the redox stability of the body ( Sang et al, 2024 ; Zhang et al, 2024 ). Studies have shown that testicular I/R damage is related to the decrease in antioxidant enzymes regulated by Nrf2 ( Antonuccio et al, 2022 ). Indeed, the use of some antioxidants (including SAL) has been extensively discussed for preventing testicular injury ( Matzkin et al, 2021 ; Cai et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of an antioxidant, e.g., Zinc, can lead to the activation of the Nrf2 pathway in rats with testicular I/R damage by reducing the expression of miR-101-3p [ 122 ]. The findings show that the use of antioxidants such as Idebenone (IDE), selenium (Se), and MitoQ, in spermatic cord torsion/detorsion models can improve Nrf2/Keap1 signaling translocation from the cytoplasm to the nucleus and regulate the Nrf2 levels to counteract with oxidative stress [ [123] , [124] , [125] ]( Fig. 5 )( Table 2 ).…”
Section: Role Of Nrf2 In Female and Male Infertility Disordersmentioning
confidence: 99%
“…In particular, HIF-1α, the active subunit of HIF-1, regulates the physiological activity and the expression of this factor. In testis, HIF-1α is present under both normoxia and ischemia [7]. An evident increase in its expression was shown in experimental models of ischemia/reperfusion [7,8], even if its role has not yet been completely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In testis, HIF-1α is present under both normoxia and ischemia [7]. An evident increase in its expression was shown in experimental models of ischemia/reperfusion [7,8], even if its role has not yet been completely elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation